2017
DOI: 10.1371/journal.pone.0184140
|View full text |Cite
|
Sign up to set email alerts
|

The association between social capital and HIV treatment outcomes in South Africa

Abstract: BackgroundHIV treatment has reduced morbidity and mortality. By 2012, it was estimated that 60.4% of eligible South Africans accessed antiretroviral treatment; however, treatment adherence and retention remain the greatest challenges. There is a growing belief that social capital, seen as "the features of social organization that facilitate cooperation for mutual benefit", is important in promoting HIV treatment retention. The aim of this study was to establish whether social capital is associated with HIV tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…A recent study reported similar findings in Botswana comparing a population-based sample of HIV-infected and -uninfected individuals [59]. Other studies have evaluated long-term mortality risk in HIV-infected individuals in sub-Saharan Africa [11][12][13][14][15], and a few have examined the impact of individual level contextual factors [16,17]. Unlike PS: with propensity score adjustment; CD4 MI: with CD4 multiple imputation; HR: adjusted hazard ratio; Base: baseline analysis without propensity score adjustment or CD4 multiple imputation.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A recent study reported similar findings in Botswana comparing a population-based sample of HIV-infected and -uninfected individuals [59]. Other studies have evaluated long-term mortality risk in HIV-infected individuals in sub-Saharan Africa [11][12][13][14][15], and a few have examined the impact of individual level contextual factors [16,17]. Unlike PS: with propensity score adjustment; CD4 MI: with CD4 multiple imputation; HR: adjusted hazard ratio; Base: baseline analysis without propensity score adjustment or CD4 multiple imputation.…”
Section: Discussionmentioning
confidence: 61%
“…We and others have found, however, that contextual factors (e.g. barriers to care), emotional health, social support, and competing needs at the time of diagnosis, also likely to have an important effect on survival [16,17]. In addition, most mortality studies, including those that have examined social and contextual factors, have limited analyses to HIV-infected individuals [7,[18][19][20][21][22][23].…”
mentioning
confidence: 93%
“…While our results showed that a few components of social capital (eg, if the participant had trust in people in general and if the participant felt that people in general can get hurt) provided more loading to the principle component, they were not independently associated with the pathway indicators in binary analysis. However, social capital has been found important in promoting health globally, with associated effects on both health outcomes of people living with HIV/AIDS [15] and child nutritional status [14]. According to Ogden et al [13] the process of building social capital can support health policy and health system strengthening by creation of trust, norms of reciprocity, rights and sanctions across the health system and reaching into the community.…”
Section: Discussionmentioning
confidence: 99%
“…Yet cheap and effective tools exist for most childhood infections [12], many which are included in the kit used by the APEs in Mozambique. Lack of social capital, i.e, the (usually non-monetary) resources generated through social networking and involvement in community affairs (eg, sense of belonging, trust and influence) [13], has also shown to be associated with poorer health outcomes and behaviours [14,15]. While social capital as a concept is increasingly being used to help policy-makers and programmers understand how formal and informal networks within and among communities can foster better governance and accountability, as well as contribute to improvements in health, health financing and the equitable delivery of health services [13], it has never been explored in the context of understanding care seeking patterns for child deaths.…”
mentioning
confidence: 99%
“…Earlier studies on ART treatment indicated that there were some poor outcomes among those initiating ART under set criteria as CD4 and WHO clinical stage. These poor outcomes reported include, high death and lost to follow up (LTFU) rates among those initiating ART [ 13 , 14 ], delayed ART initiation [ 6 , 7 ], inadequate adherence to ART [ 15 , 16 ] and below target levels of viral load suppression [ 6 , 15 , 17 ]. In Uganda specifically, the viral load suppression has remained at 56.0%, much less than the UNAIDS2020 target of 90%, amidst the various interventions put in place, including test and treat [ 1 ].…”
Section: Introductionmentioning
confidence: 99%